Research on Reducing the Energy Intensity of the Drive System of a Wheelchair Equipped with an Assisted Uphill Module - Bartosz Wieczorek; Łukasz Warguła (Applied Sciences)
This study examines the impact of the reversing interlock module on the energy intensity of manual wheelchair propulsion while considering the need for the module to cooperate with wheels exhibiting significant roundness deviations. The aim was to determine the additional energy demand caused by the module and analyze the effect of the number of one-sided ribs in flexible rollers on energy consumption. Experiments were conducted on a specially designed test bench to measure the torque, power, and energy required to rotate the wheels. The results show that the use of flexible rollers reduces energy consumption compared to rigid rollers—by 8% at a clamping force of 10 N and by 13% at 100 N. A linear relationship between the clamping force and energy savings, along with a significant influence of the roller rotation direction, was observed. When rotating in the less rigid direction, a 17% reduction in energy intensity was achieved. These findings suggest that incorporating flexible rollers in the reversing interlock module can significantly enhance the energy efficiency of wheelchairs.